Strategic Considerations for First-Time Sovereign Bond Issuers - Polan, Magdalena (IMF Working Papers; Working Paper ;, 2008)
The recent round of debt relief has restored debt sustainability in many low-income countries (LICs). This, along with a continued search for yield and desire for portfolio diversification by investors, has increased the range of viable financing options, including international bonds, for many emerging market (EM) economies and LICs. This paper presents some of the advantages and disadvantages of international debut bonds, within a debt sustainability framework. It outlines key preconditions and discusses strategic considerations that countries need to take into account when contemplating bond issuance in international markets for the first time. In this context, the paper also discusses some typical pitfalls in accessing international capital markets, including excessive issue size relative to the intended use of bond proceeds, issuance of bullet bonds, and inadequate preparation for accessing the markets.